Medicine : the definitive illustrated history - Parker, Steve 1952- (Dorling Kindersley Limited, 2016)
Tells the fascinating history of medicine through the ages to the present day. Follow the greatest stories of medicine and its breakthroughs, with incredible coverage of disease, drugs, treatment, and cures. Medicine covers the gory pitfalls and miraculous breakthroughs of medical history from trepanning, bloodletting, and body snatching to brand new developments in IVF and gene therapy with compelling stories and stunning illustrations. Clear diagrams explain major diseases such as cancer, and trace the progression of medical treatment through the centuries, from ancient healers and herbalists to scurvy and smallpox, and the World Wars to modern psychiatry